NONLINEAR PHOTONIC CRYSTAL FOR ALL-OPTICAL SWITCHING APPLI - Ayi Bahtiar; Yayah Yuliah -; Irwan Ary Dharmawan (Bionatura, 2007)
An all-optical switching device is a crucial component for developing high speed data transmission and signal processing in telecommunication network. The device is based on nonlinear optical material, whose refractive index depends on light intensity. Recently, photonic crystals have been considerable interest both theoretically and experimentally for optical switching devices. Due to the practical reason, we studied one-dimensional nonlinear photonic crystal for all-optical switching devices. We use transfer matrix method and nonlinear coupled mode equation to determine photonic bandgap and optical switching process. We applied them to different structures: nonlinear Distributed Bragg Reflector (DBR) and nonlinear photonic crystals which has similar linear refractive index but has opposite sign of nonlinear refractive index. By using an appropriate combination of refractive indices, it was found that the first structure can be used for all-optical switching at telecommunication wavelength (1.55 m). The second structure can be used both for all-optical switching and optical limiter at the wavelength of 1 m.Keywords: all-optical switching, optical limiter, nonlinear photonic crystal, transfer matrix, nonlinear coupled mode equation.